Social intelligence and pathological gaming: a longitudinal study of the associations among negative emotions, social intelligence, aggression, and pathological gaming in adolescents - Lee, Sung Je; Jeong, Eui Jun; Choi, Jae In; Park, Man Su (Frontiers in Psychiatry, 2024)
Pathological gaming continues to be highlighted as one of the most crucial issues related to young adolescents. Many studies have demonstrated the relationships among adolescents' negative emotions (e.g., stress and anxiety), social factors (e.g., social skill and relationships) and pathological gaming. For young adolescents, social intelligence has been one of crucial concepts in relation with social factors. However, there have been few studies on pathological gaming in conjunction with social intelligence through longitudinal analyses. Previous studies showed that the social intelligence of adolescents can be significantly influenced by negative emotions, and could affect the degrees of aggression and pathological gaming. This study explored the associations among adolescents' negative emotions (stress, anxiety, and loneliness), aggression, social intelligence, and pathological gaming based on the three-year data from Korean adolescent gamers (N=968) by examining a structural equation model. The results revealed that the level of social intelligence was decreased by negative emotions and diminished the degree of aggression, ultimately shrank the degree of pathological gaming. Negative emotions decreased social intelligence while they increased the level of aggression. In particular, social intelligence affected aggression much stronger than negative emotions. Results and implications were discussed.